2015
DOI: 10.3892/or.2015.3828
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding motif protein 5 negatively regulates the activity of Wnt/β-catenin signaling in cigarette smoke-induced alveolar epithelial injury

Abstract: Abstract. Cigarette smoking is closely associated with various respiratory diseases. Oxidants and carcinogens in cigarettes are reported to induce various airway epithelial injuries. However, the underlying mechanisms remain unclear. The aims of the present study were to determine the involvement of RNA-binding motif protein 5 (RBM5) and Wnt/β-catenin signaling in cigarette smoke-induced alveolar epithelial injury, as well as the interaction between both. A549 cells were treated with cigarette smoke extract (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Also, it was shown to inhibit canonical Wnt/β-catenin signaling [14]. So, we determined the critical molecules in both apoptosis and Wnt/β-catenin signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was shown to inhibit canonical Wnt/β-catenin signaling [14]. So, we determined the critical molecules in both apoptosis and Wnt/β-catenin signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In early research, RBM5 was reported to regulate the splicing of an apoptotic factor Fas and resensitize lung cancer cells A549 to cisplatin [13]. Also, RBM5 was shown to inhibit Wnt/β-catenin signaling in A549 cells [14]. Wnt/β-catenin signaling was vital to cancer cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…RBM5-mediated apoptosis is associated with up-regulation of the proapoptotic protein B-cell leukemia/lymphoma 2-associated X, downregulation of the antiapoptotic proteins B-cell leukemia/ lymphoma 2 and B-cell leukemia/lymphoma 2-like 1, increased release of mitochondrial cytochrome c into the cytosol, and increased activation of caspases 9 and 3 (13,38,51). Previous research has shown that the overexpression of RBM5 inhibited canonical Wnt-b-catenin signaling and regulated cell apoptosis (14,15). However, the role of RBM5 in BUC remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…RBM5 was most frequently reported to induce apoptosis by regulating caspase-2 and Fas alternative splicing (6,17). Furthermore, it was shown to inhibit canonical Wnt-bcatenin signaling (14,15). Consequently, we determined the critical molecules involved in both the apoptosis and Wnt-b-catenin signaling pathways.…”
Section: Rbm5 Induces Bladder-cell Apoptosis By Depressing B-catenin mentioning
confidence: 99%
See 1 more Smart Citation